Analisis kadar logam berat pada alga merah (Gracilaria sp) di Area Pelabuhan Larea-rea Kecamatan Sinjai Utara Kabupaten Sinjai - Syafaat, M. Aidin; Rukmana, Rusmadi; Masri, Mashuri; Latif, Ulfa Triyani A.; Dirhamzah, Dirhamzah (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2024)
Red algae (Gracilaria sp) is a type of red seaweed that is widely cultivated in Sinjai Regency because it has high economic value and is easy to cultivate. This study aims to determine the types and concentrations of heavy metals contained in red algae (Gracilaria sp) cultivated in the Larea-rea Port area, North Sinjai District, Sinjai Regency. The research method used was the purposive sampling method at four points and analyzing the heavy metal content was carried out using the Atomic Absorption Spectrophotometer (AAS) method. The research location consists of four points, namely near Larea-rea Port (point 1), far from residential areas (point 2), near residential areas (point 3) and near residential areas and river estuaries (point 4). The results showed that the heavy metals contained in red algae were lead (Pb), cadmium (Cd) and mercury (Hg). The concentration of Pb metal in red algae with the highest value is at point 4, which is 1.971 mg/kg with a high pollution category. The Cd content with the highest value is at point 3, which is 0.046 mg/kg, including the low pollution category. While the Hg content with the highest value is at point 1, which is 0.08 mg/kg, including the low pollution category. Environmental parameters that influence this study are salinity and pH.